4 Embedding improvement science across an organization: Our four-year journey. (29th July 2022) - Butler, Alison; Edwards, Simon
Abstract : Introduction: The organization (CNWL) has services in over 150 locations and tried multiple improvement approaches in the past (with limited success). Can we embed improvement science across the organization in four years? Adopting a single methodology, focusing on co-production, data literacy, targeted training and a communication strategy to celebrate success. Methods: Our theory was, if we focused on the following four areas from the outset we would be successful at embedding improvement science. Worked with service users and carers to design, develop and deliver our strategy Changed how we use data (RAG reporting to SPC charts) in all board reports. Developed a dosed training programme as well as targeting key influential leaders Celebrated success, generated improvement stories and developed an annual conference with poster presentations and prizes We also set ourselves a target of achieving 80% service user and carer involvement (in four years). Results: Some of our results: 2548 staff trained in QI methodologies (36% of the workforce) 64% of our QI projects now have service user and carer involvement 283 active projects 90% of our committee papers contain SPC charts Improved staff satisfaction and morale Putting co-production at the forefront of our roll-out has changed the dial on service user/carer involvement across the organization with significant improvements demonstrated in previously difficult to improve areas. Our first ever annual conference attracted 430 people and 170 posters, evidencing the enthusiasm for sharing their improvement across the organization. Following this success, we developed an Improvement Academy. Discussion: Co-production on delivery, design and implementation is pivotal to success. Nile Ward Psychiatric Intensive Care Unit, London, gives an example of how it used co-production to develop a set of mutual expectations between staff and patients to reduce violence on the unit. 2 Developing bespoke training to meet needs of key staff groups has enormous impact. Prioritise embedding SPC charts into board reports from the start. In Making Data Count, S. Riley writes, 'There is strong evidence that better decisions are made when using SPC rather than 'simple' techniques such as the popular RAG approach'. 1 Opportunities for staff to share their work at a conference generates organizational enthusiasm for QI. 3 References: 'Making data count', NHS Improvement, Riley S. Jan 2019. Rahman. M, Taylor, C. Abdullahi. R, Okwuokei. A, Waugh. M, Kaji. M, Magadlela. B. Nile Ward PICU violence reduction quality improvement project. BJPsych Open June 2021;7 (S1). Winning posters submissions for the CNWL Safety Conversation Day https://www.cnwl.nhs.uk/news/safety-conversation-cnwl-excellent-patient-care-flourishes-open-and-honest-environment